1982
DOI: 10.1007/bf01870769
|View full text |Cite
|
Sign up to set email alerts
|

An ATP-driven proton pump in brush-border membranes from rat renal cortex

Abstract: The rate of ATP hydrolysis in ATP-preloaded plasma membrane vesicles derived from the luminal membrane of renal cortical tubules, and the rate of H+ secretion out of the same vesicles were investigated. Both were inhibited at low temperature, by the action of filipin, an antibiotic that complexes with cholesterol in plasma membranes, and by the action of blockers of mitochondrial Fo hydrogen channels, dicyclohexylcarbodiimide and Dio-9. Valinomycin in the presence of K+ showed a stimulatory effect, the protono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(32 citation statements)
references
References 46 publications
7
24
1
Order By: Relevance
“…These results suggest that the endocytic vesicles budding off the brush border of the proximal tubule are acidified at least in part by proton pumps, rather than exclusively by Na'-H' exchangers, and respond to CO2 by fusing with the luminal membrane. Previous studies by Kinne-Saffran et al (20) and one of us (11) have also suggested that the proximal tubular brush border contains a H' pump. What is not clear is the quantitative role that such a pump might play in net H' secretion in this segment.…”
Section: Resultsmentioning
confidence: 63%
“…These results suggest that the endocytic vesicles budding off the brush border of the proximal tubule are acidified at least in part by proton pumps, rather than exclusively by Na'-H' exchangers, and respond to CO2 by fusing with the luminal membrane. Previous studies by Kinne-Saffran et al (20) and one of us (11) have also suggested that the proximal tubular brush border contains a H' pump. What is not clear is the quantitative role that such a pump might play in net H' secretion in this segment.…”
Section: Resultsmentioning
confidence: 63%
“…However, several groups have found that luminal Na' removal does not eliminate all acidification (67). At least one group also finds a H' translocating ATPase in brush border membranes (69). This ATPase activity may be due to contamination from intracellular vesicles, many of which contain H' ATPases.…”
Section: Transepithelial Ion Transportmentioning
confidence: 99%
“…Bicarbonate absorption in the rat proximal convoluted tubule is mediated on the apical membrane by a Na/H antiporter and a Na-independent, amiloride-insensitive mechanism, most likely a H-translocating ATPase (1)(2)(3)(4)(5)(6)(7)(8)(9). Base generated within the cell exits across the basolateral membrane via a Na(HCO3)3 symporter (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%